2021
DOI: 10.5620/eaht.2021023
|View full text |Cite
|
Sign up to set email alerts
|

Pollution investigation and risk assessment of polycyclic aromatic hydrocarbons in soil and water from selected dumpsite locations in rivers and Bayelsa State, Nigeria

Abstract: The transfer ratio of polycyclic aromatic hydrocarbons (PAHs) from soil dumpsite to borehole water is dependent of polluting source and exposure matrices that causes immerse health risk to man and environment over a period of time. PAHs were assessed in selected soil dumpsite and borehole water located at Rivers state (Eleme, Eliozu, Eneka, Oyigbo, and Woji) and Bayelsa state (Yenagoa), Nigeria. Soil samples were collected at four different points 30 m (North, South, East and West) locations at a depth of 15 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Crude oil pollution is currently considered to be a great threat to the health of living things in the environment including humans. Nigeria records an average of 300 oil spills in the oil producing States annually, making the Niger Delta regions the most polluted part of Nigeria, affecting the air, soil and water bodies [24]. Early reports estimated that about 0.08 to 0.4% of the internationally produced crude oil is spilled into the environment [25].…”
Section: Resultsmentioning
confidence: 99%
“…Crude oil pollution is currently considered to be a great threat to the health of living things in the environment including humans. Nigeria records an average of 300 oil spills in the oil producing States annually, making the Niger Delta regions the most polluted part of Nigeria, affecting the air, soil and water bodies [24]. Early reports estimated that about 0.08 to 0.4% of the internationally produced crude oil is spilled into the environment [25].…”
Section: Resultsmentioning
confidence: 99%
“…The pollutants are present in concentrations that may be toxic to different organisms [34][35][36]. The concentration of Cadmium across the study area ranged from 0.001 at sampling points B and D to 0.007 at sampling point C. The values recorded were lower than (0.043 mg/l) and (0.072 mg/l) in the water reported by Oguzie and Okhagbuzo [37].…”
Section: Discussionmentioning
confidence: 95%
“…From the present study (Table 5 and Fig. 3), the concentration of Cd, Cr, Cu, Fe, Pb, Mn, Ni, and Zn showed that hazard quotients were all less than one (1) across all alcoholic beverages, as the hazard index (total hazard quotient) showed that H (1.48) and PW (1.89) were above one (1), which implies signi cant health effect or illness is possible for a period of time, whereas HG (0.51), IRW (0.80), IDG (0.73), LDG (0.75), GS (0.80) and W (0.97) were less than one (1) indicating no apparent potential health risk such as intoxication, drunkenness, vomiting, overdose in tandem to death, oxidative damage, chronic in ammatory diseases, premature aging and lung embolism [59,75,[89][90][91].…”
Section: Table 5 About Herementioning
confidence: 99%
“…The cancer risk (Table 5) evaluates the incremental chance that a respondent (adult) develops cancer-based issues over a period of time from a carcinogen [89,91]. As we can see, the risk total (Fig.…”
Section: Table 5 About Herementioning
confidence: 99%